The Effect of Nitrogen Fertilizer Dosage on Disease Severity for Growth and Production of Rice Plants - La Ode Muhamad Yusril; La Ode Santiaji Bande; Asmar Hasan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Nitrogen fertilizer is important in increasing rice yields, but the proper dosage must be considered to maximize the results and reduce the risk of disease attacks. The study aimed to assess how various nitrogen fertilizer dosages affected disease severity, plant growth, and rice production. This research was conducted in the Village of lebo Jaya, Region of Konda, South Konawe Regency, applying a block design that is randomized (RAK). The experiment included six treatments and three replications, namely without fertilization (P0), 50 kg/ha-1 Urea, 300 kg/ha-1 Phonska (essential fertilizer), 100 kg/ha-1 Urea, 150 kg/ha-1 Urea, and 200 kg/ha-1 Urea. The variables observed included the severity of blast disease (Pyricularia oryzae) and bacteria blight (Xanthomonas oryzae pv. oryzae), plant height, number of leaves, number of tillers, panicle length, number of grains per panicle, weight of grain per panicle, percentage of filled grain per panicle, weight of grain per clump, weight of 1000 grains, and rice production. The study's findings showed that the dose of nitrogen fertilizer, Both 150 and 200 kg of urea/ha, had a positive effect on growth and production, increasing plant height, number of leaves, number of tillers, the weight of 1000 grains (36.00 g), and grain production (4.83 tons/Ha). In addition, the 100 kg /ha-1 Urea doses and 150 kg /ha-1 Urea tended to reduce the severity of bacterial leaf blight and blast diseases. Therefore, applying the 200 kg/ha-1 increased rice yields, while a 100 kg/ha-1 dosage could reduce the disease risk.